2002
DOI: 10.2329/perio.44.168
|View full text |Cite
|
Sign up to set email alerts
|

Factors in Physiological Breath Odor.

Abstract: To identify factors associated with "morning breath" (physiological breath odor preceding breakfast) in healthy adults, we assessed breath odor, analyzed intraoral factors, and collected saliva and tongue coat samples incubated to ascertain the relationship between intraoral bacteria and breath odor. Subjects were 44 healthy men with a mean age of 24.1 years.The breath odor of each was assessed by an organoleptic test and quantified using a portable sulphide monitor (Halimeter RH-17 E(R)) and gas chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…VSC measurements VSC analysis was performed by gas chromatography according to the method of Saito et al 5 The amounts of hydrogen sulfi de (H 2 S), methyl mercaptan (CH 3 SH), dimethylsulfi de ((CH 3 ) 2 S), and the total for all three (total VSCs) were measured with a portable sulfi de monitor (Halimeter RH-17, Interscan, Chatsworth, CA, USA). The Halimeter measurements were performed according to the method of Satoh et al 21 …”
Section: Organoleptic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…VSC measurements VSC analysis was performed by gas chromatography according to the method of Saito et al 5 The amounts of hydrogen sulfi de (H 2 S), methyl mercaptan (CH 3 SH), dimethylsulfi de ((CH 3 ) 2 S), and the total for all three (total VSCs) were measured with a portable sulfi de monitor (Halimeter RH-17, Interscan, Chatsworth, CA, USA). The Halimeter measurements were performed according to the method of Satoh et al 21 …”
Section: Organoleptic Methodsmentioning
confidence: 99%
“…In 1999, a Japanese Ministry of Health and Welfare survey conducted on approximately 30 000 Japanese citizens reported that, after periodontal disease and tooth decay, 14.5% of the respondents were concerned about halitosis. 1 Various causes of halitosis have been identifi ed: it can originate in the oral cavity such as from severe tooth decay, 2 periodontal disease, 3,4 and tongue plaque; [4][5][6] in the ear, nose, and throat, including from diseases such as paranasal sinusitis, chronic rhinitis, and chronic tonsillitis; 7 and it can originate from other diseases such as diabetes 8 and renal failure, 9,10 albeit more rarely. 11 Meanwhile, several reports have described the presence of halitosis even without any particular oral or systemic disease, such as upon wakening in the morning, or associated with an empty stomach or being tired.…”
Section: Introductionmentioning
confidence: 99%
“…Counting was repeated 3 times and the mean value was calculated. To assess bad breath, air from the oral cavity was collected with a syringe and H 2 S concentration was determined using Oral Chroma CHM-2® (FIS, Osaka, Japan) [12] . The data were compared between before and after cleaning in Study 1.…”
Section: Methodsmentioning
confidence: 99%
“…These data have been clarified recently by the development of gas chromatography (GC) [8][9][10] and flame photometric detectors (FPD) 11,12) . Saito et al reported that the amounts of these substances correlated with the total number of bacteria and the number of streptococci, aerobic and anaerobic bacteria in tongue coat 6) .There are some reports of the bacteria in tongue…”
mentioning
confidence: 99%